Viability of Harvesting Salinity Gradient (Blue) Energy by Nanopore-Based Osmotic Power Generation. (February 2022) - Wang, Zhangxin; Wang, Li; Elimelech, Menachem
Abstract: The development of novel materials with ion-selective nanochannels has introduced a new technology for harvesting salinity gradient (blue) energy, namely nanopore power generators (NPGs). In this study, we perform a comprehensive analysis of the practical performance of NPG in both coupon-size and module-scale operations. We show that although NPG membrane coupons can theoretically generate ultrahigh power density under ideal conditions, the resulting power density in practical operations at a coupon scale can hardly reach 10 W·m −2 due to concentration polarization effects. For module-scale NPG operation, we estimate both the power density and specific extractable energy (i.e., extractable energy normalized by the total volume of the working solutions), and elucidate the impact of operating conditions on these two metrics based on the interplay between concentration polarization and extent of mixing of the high- and low-concentration solutions. Further, we develop a modeling framework to assess the viability of an NPG system. Our results demonstrate that, for NPG systems working with seawater and river water, the gross specific extractable energy by the NPG system is very low ( 0.1 kW·h·m −3 ) and is further compromised by the parasitic energy consumptions in the system (notably, pumping of the seawater and river water solutions and their pretreatment). Overall, NPG systems produce very low net specific extractable energy (< 0.025 kW·h·m −3 ) and net power density (< 0.1 W·m −2 ). Our study highlights the significant practical limitations in NPG operations, casting doubt on the viability of NPG as a technology for blue energy harvesting.